2020
DOI: 10.7759/cureus.11531
|View full text |Cite
|
Sign up to set email alerts
|

Sciatic Nerve Variants and the Piriformis Muscle: A Systematic Review and Meta-Analysis

Abstract: The present systematic review and meta-analysis provides a comprehensive assessment of the sciatic nerve (SN) variants relative to the piriformis muscle (PM) and compares those variants' prevalence among different geographical populations with respect to gender and laterality. A database search was conducted to identify cadaveric studies pertinent to SN variants relative to the PM. A total of 44 articles were included. The typical morphological pattern (type A, with the SN passing undivided below the PM) was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…As it traverses from the low back posteriorly to the lower limb through the greater sciatic foramen and progresses distally in the posterior thigh compartment, it splits into two branches (tibial nerve and common peroneal nerve) just before the popliteal fossa. 98 The SN and…”
Section: General Techniques: Approaches To Nerves Sciatic Nerve (Sn)mentioning
confidence: 99%
See 1 more Smart Citation
“…As it traverses from the low back posteriorly to the lower limb through the greater sciatic foramen and progresses distally in the posterior thigh compartment, it splits into two branches (tibial nerve and common peroneal nerve) just before the popliteal fossa. 98 The SN and…”
Section: General Techniques: Approaches To Nerves Sciatic Nerve (Sn)mentioning
confidence: 99%
“…As it traverses from the low back posteriorly to the lower limb through the greater sciatic foramen and progresses distally in the posterior thigh compartment, it splits into two branches (tibial nerve and common peroneal nerve) just before the popliteal fossa. 98 The SN and its divisions provide sensory innervation to the foot and lower extremity except for the medial leg and ankle which are supplied by the saphenous nerve.…”
Section: Summary Of Literaturementioning
confidence: 99%
“…Barbosa et al [ 23 ] conducted a systematic review and showed that the most prevalent anatomical variation was that the common fibular nerve passed through the piriformis muscle fibers (33.3%) and pointed to a possible association of this condition with piriformis syndrome. Similarly, Poutoglidou and colleagues [ 24 ] wrote a comprehensive systematic review with a meta-analysis of the SN variants relative to the PM and compared those variants’ prevalence among different geographical populations with respect to gender and laterality, reporting that SN variants were more common among East Asians (with a 31% pooled prevalence of total variants), and no statistically significant differences with respect to gender and laterality.…”
Section: Discussionmentioning
confidence: 99%
“…Until recent years, pseudo‐sciatica or localized pain in the buttock, with or without radiation to the thigh, has been related to sciatic entrapment at the level of the piriformis muscle (Piriformis syndrome) (Hopayian et al, 2010), especially when the sciatic nerve has a variant anatomy (Poutoglidou et al, 2020). Pećina (1979) found that in 6.15% of cases the nervus peroneus communis passes between the tendinous parts of the piriformis, and they considered this variation of practical significance for the development of “piriformis syndrome.” During internal rotation of the thigh, the piriformis is extended, and the tendons of the divided muscle are tightly pressed together, pinching the nerve between them.…”
Section: Discussionmentioning
confidence: 99%
“…Until recent years, pseudo-sciatica or localized pain in the buttock, with or without radiation to the thigh, has been related to sciatic entrapment at the level of the piriformis muscle (Piriformis syndrome) (Hopayian et al, 2010), especially when the sciatic nerve has a variant anatomy (Poutoglidou et al, 2020). Pe cina (1979) found that in 6.15%…”
Section: Discussionmentioning
confidence: 99%